2011
DOI: 10.4097/kjae.2011.61.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of an adult patient with Rett syndrome and limited mouth opening -A case report-

Abstract: Rett syndrome is a neurological disease that occurs only in females and it manifests with mental retardation, seizures, movement disorders, autistic behavior and abnormal breathing. A 19-year-old female with Rett syndrome underwent ophthalmologic surgery under general anesthesia at our institution. Airway control was difficult due to her limited mouth opening. We recommend that anesthesiologists should have proper knowledge about this disease and the patients to avoid the complications and problems that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…Anecdotal evidence and case reports exist describing the sensitivity of patients with Rett syndrome to opioids and benzodiazepines and delayed recovery from anesthesia. 11 -17 Tofil et al 17 showed that individuals with Rett syndrome require lower doses of propofol and take longer to breathe independently after propofol exposure. The breathing irregularities described above, combined with sensitivities to analgesics that suppress the respiratory drive, may lead to longer intensive care unit stays and increased respiratory infection rates.…”
mentioning
confidence: 99%
“…Anecdotal evidence and case reports exist describing the sensitivity of patients with Rett syndrome to opioids and benzodiazepines and delayed recovery from anesthesia. 11 -17 Tofil et al 17 showed that individuals with Rett syndrome require lower doses of propofol and take longer to breathe independently after propofol exposure. The breathing irregularities described above, combined with sensitivities to analgesics that suppress the respiratory drive, may lead to longer intensive care unit stays and increased respiratory infection rates.…”
mentioning
confidence: 99%
“…RS may be extremely susceptible to sedative agents, opioids, and volatile anesthetics, and thus, the risk of perioperative respiratory complications from delayed awakening to apnea may increase [ 3 5 ]. In a retrospective case-controlled study by Tofil et al, postoperative prolonged apnea was observed in 7 of 21 patients with RS [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Her Mallampati score was class I and her mouth was wide enough to allow the insertion of two fingers. She A previous case regarding the anesthetic management of a patient with Rett syndrome was reported in our country [6].…”
mentioning
confidence: 98%